Job-Related Stress: An Analysis on Stressors for Indian Police Force: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Stress has become one of the major concerns of present times. Most of the time, we are under stress of some sort or other. Most of the time stress at work, stemming from increasing job complexity and its divergent demands, which has become pervading features of modern organizations. A little amount of stress may be helpful from organizational and personal point of view. It is reported that stress creates as well as promote employee's inclination towards the job, thus enhances the performance and develops positive attitudes among employees.